2017
DOI: 10.1080/09589236.2017.1296352
|View full text |Cite
|
Sign up to set email alerts
|

‘Feel what I feel’: making da(r)ta with teen girls for creative activisms on how sexual violence matters

Abstract: To cite this article: Emma Renold (2018) ABSTRACTInspired by feminist new materialist and posthuman activist philosophy, this paper speculates on what happens when data entangles with artsbased methodologies in a school-based participatory activist project with six teen girls (age 15) on gender-based and sexual violence. Mapping the journey of how data become da(r)ta and how da(r)ta become d/artaphacts, the paper follows how the Runway of Disrespect, the Shame Chain, the RulerSkirt and the Tagged Heart ripple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 46 publications
0
112
0
2
Order By: Relevance
“…Spyrou’s questions about ‘what kind of children (and others) emerge out of children’s entanglement with the material and discursive worlds in which their lives are embedded … which material‐semiotic arrangements … make certain perspectives, voices, or standpoints possible’ (p 318, this volume), are highly pertinent to understanding the Children’s Strike. Since description — as our contributors remind us — is ontological politics, the vocabularies of enactment, intra‐action, assemblage, entanglement, emergence and multiplicity that these perspectives offer not only to shed new light on how to read young people’s activisms (see also Renold, ) but may also allow us to act differently in the world.…”
Section: On Inclusivity and Interdisciplinaritymentioning
confidence: 99%
“…Spyrou’s questions about ‘what kind of children (and others) emerge out of children’s entanglement with the material and discursive worlds in which their lives are embedded … which material‐semiotic arrangements … make certain perspectives, voices, or standpoints possible’ (p 318, this volume), are highly pertinent to understanding the Children’s Strike. Since description — as our contributors remind us — is ontological politics, the vocabularies of enactment, intra‐action, assemblage, entanglement, emergence and multiplicity that these perspectives offer not only to shed new light on how to read young people’s activisms (see also Renold, ) but may also allow us to act differently in the world.…”
Section: On Inclusivity and Interdisciplinaritymentioning
confidence: 99%
“…After this, we moved towards an explicit focus on gender, discussing gender as identity; stereotypes and expectations; popular culture; gendered forms of violence; and gender-based activisms. We finished by inviting young people to offer messages for change on (how) 'gender jars' using paper, pens and a glass jar (see Renold 2018). In this paper, we prioritise young people's narrative reflections on how (far) language, identities, bodies, images, objects, emotions and social relations and relationships are gendered and/or imbued with gendered meanings in the context and practices of their everyday lives.…”
Section: Researching Young People's Contemporary Experiences Of How Gmentioning
confidence: 99%
“…In this paper, we include data from the latter only if participants were aged 12-14. 3 Our participatory research also involved working with a diverse self-identified 'feminist' advisory group (age 14-17) to co-create a series of activities informed by creative and visual methods (Mannay 2016;Renold 2018). 4 Our methodology is informed by feminist and queer approaches to gender, specifically theories and concepts that pay attention to the performative (Butler 2004), situated (Haraway 1988) and intersectional (Crenshaw 1991) ways in which gender is experienced as always in process and mediated across seemingly sedimented, yet unstable, discursive, material, temporal, corporeal and affective terrains (Braidotti 2002).…”
Section: Researching Young People's Contemporary Experiences Of How Gmentioning
confidence: 99%
“…PhEmaterialism, an assemblage itself of posthumanism, multiple feminisms and (new) materialism, strives to re-mix and re-imagine "habitual relationalities…" to move "educational research somewhere different than before" (Ringrose et al, 2019, p. 1). In other words, PhEmaterialism entangles multiple theories (and methods) to generate "new ways of doing" (ibid, p. 1) while simultaneously slowing down and reconfiguring what counts as research engagement (Renold, 2018). It offers the world as nonlinear, complex and shifting and, in doing so, activates all bodies (humans, materials, emotions, thoughts) to be productive (Niccolini, Zarabadi, & Ringrose, 2018).…”
Section: A 'Prologue'mentioning
confidence: 99%
“…During this week, four Black and Latinx youth and I interacted with health and fitness related magazines, knowledge(s) and materials. Thus, in reimagining what 'matters' through an affective lens, this paper became an 'experiment' -an unforeseen inquiry into collaging that arose from wonder (MacLure, 2013a), doubt (Holbrook & Pourchier, 2014), and slowness (Renold, 2018). This wonder, doubt and slowness were themselves produced through the affective potential of a magazine re-assembling, which I will discuss after a brief background on the project itself.…”
Section: What Does This Paper Do?mentioning
confidence: 99%